Atherosclerosis - the multifactors disease - Berek, Kinga; Bobiński, Rafał (Nursing Problems / Problemy Pielęgniarstwa, 2009)
Atherosclerosis is a complex, dynamic pathological process, whose basis is the chronic inflammatory state which involves intimal layer arteries. Classic risk factors like: age, gender, elevated cholesterol concentration, arterial hypertension, cigarette smoking, abuse of alcohol, diabetes, low physical activity, obesity, stress, infectious-inflammatory factors and hyperhomocysteinemia play an important role in the development of atherosclerotic changes. The clinical symptoms of atherosclerosis usually appear later in life. Sometimes the changes of vessels may have their origin in an early childhood, therefore early detection of the main risk factors is important to prevent their progression.